Selling Collectibles on eBay - Miller, Michael, 1958- (Que, 2006)
Of all the categories of products for sale on eBay, the collectibles category is both the largest and the most complex. If you're selling a particular type of collectible - from pinbacks to Pez dispensers - how do you effectively list your products for auction and maximize your sales and profits? Selling Collectibles on eBay is a targeted, compact guide for all serious collectibles sellers. It offers instructions and advice for selling all types of collectibles, from trading cards and figurines to vintage comic books and glassware. This Digital Short Cut skips the general information you find in most eBay books and goes directly to specific issues of interest to collectibles sellers. Selling Collectibles on eBay leads the collectibles seller through all the steps of a successful eBay sale, from obtaining and identifying collectibles to sell, to grading and authenticating items, to determining valuation and pricing, to photographing various types of collectibles, to creating a collectibles-appropriate auction listing, to packing and shipping fragile items, to dealing with various collectibles-specific issues. It even includes a massive listing of acronyms and abbreviations common to collectibles auction listings. No matter what type of collectible you sell, you'll find much useful information in Selling Collectibles on eBay . Read it today - and increase your sales tomorrow!